Designing mosaic landscapes for Black Grouse Tetrao tetrix using multi‐scaled models. (16th September 2013) - Geary, Matthew; Fielding, Alan H.; Marsden, Stuart J.; Brotons, Lluis
<x xml:space="preserve">Abstract</x> With increasing pressures on land for human use, it is important to identify the habitat requirements of key species, not just in terms of a correlation with a given habitat feature, but also the relationship between species presence and its coverage, proximity to other habitat types, and importance at different spatial scales. We used maximum entropy to estimate the optimal proportions of 18 habitat types, plus elevation and habitat richness associated with the presence of leks of Black Grouse Tetrao tetrix within an 800‐km2 study area in Perthshire, Scotland. We repeated the analysis at several radii (0.2–3 km) to assess how the importance of different habitats changed with proximity to lek and scale. We then examined habitat features or combinations of features that were associated with large leks or positive lek growth. Models at all radii had satisfactory predictive power. Using response curves from maxent, we constructed ideal habitat mixes for leks at each radius. At the 2‐km radius, suitability was highest with around 20% each of three moorland types and open/mixed forestry, whereas close to leks (0.2 km), higher proportions of grouse moor and lower proportions of closed‐canopy woodland were optimal. The relationship between habitat and lek size or direction of lek growth was complex, indicating that a landscape containing large or productive leks can be the result of more than one combination of habitats. This demonstrates a degree of flexibility in designing landscapes for Black Grouse conservation, so landowners can prioritize combinations of habitats that are the most practical and/or economical, while still serving the requirements of the target species.